Evaluation of resistance of banana genotypes with AAB genome to Fusarium Wilt Tropical Race 4 in China - Zhan, Ni; Kuang, Mengyu; He, Weidi; Deng, Guiming; Liu, Siwen; Li, Chunyu; Roux, Nicolas Stephan M.; Dita Rodriguez, Miguel Angel; Yi, Ganjung; Sheng, Ou (MDPI, 2022)
Banana cultivars with the AAB genome group comprise diverse subgroups, such as Plantain, Silk, Iholena, and Pisang Raja, among others, which play an important role in food security in many developing countries. Some of these cultivars are susceptible to Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4), the most destructive pathogen threatening banana production worldwide, and some of them are still largely unknown. We evaluated the resistance of 37 banana genotypes, including Plantain, Silk, Iholena, Maia Maoli/Popoulu, Pisang Raja, Pome, and Mysore, to Foc TR4 under both greenhouse and field conditions. Genotypes from the Silk and Iholena subgroups were highly susceptible to Foc TR4. Pome and Mysore showed resistance and intermediate resistance, respectively. However, Pisang Raja ranged from susceptible to intermediate resistance. One cultivar from the Maia Maoli/Popoulu subgroup was highly susceptible, while the other displayed significant resistance. Most Plantain cultivars exhibited high resistance to Foc TR4, except two French types of cultivar, 'Uganda Plantain' and 'Njombe N°2', which were susceptible. The susceptibility to Foc TR4 of some of the AAB genotypes evaluated, especially Plantain and other cooking bananas, indicates that growers dependent on these varieties need to be included as part of the prevention and integrated Foc TR4 management strategies, as these genotypes play a crucial role in food security and livelihoods.